Living in space - Whitehouse, Patricia (Chicago, Ill Heinemann Library, 2004)
Describes how astronauts live in space, breathe, get water, foods, baths, taking out garbage, going to the bathroom, keeping fit, and sleeping
Space
Keywords: Astronauts; Space stations